2008
DOI: 10.1080/07373930802046294
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Salting and Drying on Shark (Carcharhinus sorrah) Meat Quality Characteristics

Abstract: The effect of drying method and pretreatment with salt on the properties of shark meat was investigated. Water loss during the salting step was faster with dry salting than with brine salting; however, both methods led to the same final water content at the end of the drying process. Moisture desorption isotherms showed that addition of salt prior to sun or air drying resulted in lower equilibrium moisture contents at the same water activity levels. Salting and method of drying had significant effects on the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 48 publications
1
15
1
Order By: Relevance
“…For fresh fish and çi-roz samples, the chemical composition values were determined as follows: moisture 50.1 ±1.1 mg/100g and 18.5 ±0.2 mg/100g, ash 1.3 ±0.1 mg/100g and 5.2 ±0.3 mg/100g, total protein 20.4 ±2.0 mg/100g and 38.28 ±2.0 mg/100g, total fat 25.08 ±0.8 mg/100g and 37.42 ±0.6 mg/100g. This is in agreement with the conclusions made by literature data (Guizani et al, 2008;Selmi et al, 2010;Bae et al, 2011).…”
Section: Resultssupporting
confidence: 83%
“…For fresh fish and çi-roz samples, the chemical composition values were determined as follows: moisture 50.1 ±1.1 mg/100g and 18.5 ±0.2 mg/100g, ash 1.3 ±0.1 mg/100g and 5.2 ±0.3 mg/100g, total protein 20.4 ±2.0 mg/100g and 38.28 ±2.0 mg/100g, total fat 25.08 ±0.8 mg/100g and 37.42 ±0.6 mg/100g. This is in agreement with the conclusions made by literature data (Guizani et al, 2008;Selmi et al, 2010;Bae et al, 2011).…”
Section: Resultssupporting
confidence: 83%
“…Figure 3 shows the changes of * , * , * , Δ , and NEB parameters from fresh and rehydrated samples. According to ANOVA, the luminosity ( * ) attained statistically significant differences in all the treatments, resulting in their decrease, which were observed at 95% confidence level ( < 0.05), among the mean values that resulted in two homogeneous groups (40-60-80 ∘ C and fresh), which can be explained because the luminosity was affected mainly by NaCl osmotic pretreatment [47] and the drying temperature [1,29]. The yellowness ( * ) increased during the drying temperature due to the browning [48]; that is, it was proved that the temperatures used affected the * parameter, since these ones showed significant differences ( < 0.05) in the average value for each temperature.…”
Section: Surface Color and Nonenzymatic Browning (Neb)mentioning
confidence: 99%
“…Color changes are in connection with the changes in the structural protein that bring about a difference in light dispersion properties on the surface of abalone samples, like browning reactions [47]. Figure 3 shows the changes of * , * , * , Δ , and NEB parameters from fresh and rehydrated samples.…”
Section: Surface Color and Nonenzymatic Browning (Neb)mentioning
confidence: 99%
See 1 more Smart Citation
“…WHC behaviour is influenced by physico-chemical interactions and on the setting of the product on a microstructure (Aguilera and Stanley 1999;Miranda et al 2009). Moreover, it is generally accepted that the degree of hydration is dependent on the degree of cellular and structural disruption (Guizani et al 2008). Some authors have reported that high-pressure treatment helps to reduce water loss, probably because of disaggregation and unfolding of protein and pH of the mixture (Cheftel and Culioli 1997;Butz et al 2003;TabiloMunizaga and Barbosa-Cánovas 2005).…”
Section: Polysaccharides Contentmentioning
confidence: 99%